2022
DOI: 10.1186/s12939-022-01699-0
|View full text |Cite|
|
Sign up to set email alerts
|

Advancing behavioral interventions for African American/Black and Latino persons living with HIV using a new conceptual model that integrates critical race theory, harm reduction, and self-determination theory: a qualitative exploratory study

Abstract: Background Rates of participation in HIV care, medication uptake, and viral suppression are improving among persons living with HIV (PLWH) in the United States. Yet, disparities among African American/Black and Latino PLWH are persistent, signaling the need for new conceptual approaches. To address gaps in services and research (e.g., insufficient attention to structural/systemic factors, inadequate harm reduction services and autonomy support) and improve behavioral interventions, we integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…In particular, the intervention working group focused on the need for intrinsic motivation and personal goals pertaining to HIV viral suppression as fundamental to behavior change, and the need for participants who wished to achieve viral suppression to develop durable habits to take HIV antiretroviral therapy over time. The intervention working group drew on theories of behavioral economics (described in the Introduction) and selfdetermination theory (16). Self-determination theory is a macro theory of human motivation and personality that concerns the innate and fundamental needs for autonomy (people need to feel in control of their own behaviors and goals), competence (people need to gain mastery of tasks and learn different skills), and connection or relatedness (people need to experience a sense of belonging and attachment to other people) (48).…”
Section: Procedures To Develop the Scap Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the intervention working group focused on the need for intrinsic motivation and personal goals pertaining to HIV viral suppression as fundamental to behavior change, and the need for participants who wished to achieve viral suppression to develop durable habits to take HIV antiretroviral therapy over time. The intervention working group drew on theories of behavioral economics (described in the Introduction) and selfdetermination theory (16). Self-determination theory is a macro theory of human motivation and personality that concerns the innate and fundamental needs for autonomy (people need to feel in control of their own behaviors and goals), competence (people need to gain mastery of tasks and learn different skills), and connection or relatedness (people need to experience a sense of belonging and attachment to other people) (48).…”
Section: Procedures To Develop the Scap Interventionmentioning
confidence: 99%
“…These serious and persistent racial/ethnic inequities in engagement along the HIV care continuum and in HIV health outcomes signal the need for evolution and improvements in effective behavioral intervention approaches for PWH, including for those with the greatest barriers to HIV viral suppression. Our team's past research has shed light on such behavioral interventions to address the constellation of barriers that African American/Black and Latino PWH experience to engagement along the HIV care continuum, primarily taking counseling approaches (16)(17)(18)(19). While the evidence base for the effectiveness and utility of counseling and other such behavioral interventions delivered by professional staff is robust (20,21), as technology evolves and cell phone and smartphone use increases, researchers are increasingly turning to technologyfacilitated interventions, including those that require little or no facilitation on the part of staff, called low-touch interventions (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that the caption to Fig. 2 (‘IIT-ICM core elements for ICM1’) should have read ‘Core elements and key characteristics of the Intervention Innovations Team integrated conceptual model (IIT-ICM) to guide behavioral intervention development’.…”
mentioning
confidence: 99%